Within‐population variation in an invasive fish’ sociability when associating with conspecifics or heterospecifics - Morelia Camacho‐Cervantes; Alfredo F. Ojanguren (Ecology and Evolution)
Abstract Behavioural traits are key to promote invasion success because they are easier to adjust to changing environmental conditions than morphological or life history traits. Often, research has overlooked variance in behavioural traits within populations or has assumed it to be mere noise. However, a recent focus towards individual variation of behaviour of successful invaders has revealed new and more profound insights into the invasion process. Behavioural variation within a population could lead to more successful invasions, as they include individuals with diverse behaviours, which ensures at least some individuals could be able to cope with changing conditions. The aim of this research was to examine if invasive guppies (Poecilia reticulata) present within‐population differences in their sociability (time spent associating with a shoal) when interacting with conspecifics or heterospecifics. Guppies presented significant differences in their individual tendencies to associate with conspecific or heterospecific shoals. There were among‐individual differences in the time spent shoaling with conspecifics versus heterospecifics, where most individuals did not differ in their sociability with conspecifics or heterospecifics, and only 22% of individuals presented a higher tendency to associate with conspecifics. Our results are the first to show individual differences in fish’ tendencies to associate with heterospecifics among individuals of the same population and rearing conditions. Given that associations with heterospecific natives have been found to be as beneficial as associations with conspecifics for invaders, our results contribute to the understanding of mechanisms behind heterospecific sociability between natives and invaders.